Risk and uncertainty in domestic production and prices - Hazell, Peter B. R. (International Food Policy Research Institute, 1988)
Agricultural production is typically a risky business. Farmers face a variety of price, yield, and resource risks which make their incomes unstable from year to year. In many cases farmers are also confronted by the risk of catastrophe. For example, crops may be totally destroyed by hurricane, fire, drought, pests, or diseases, and product prices may plummet because of structural adjustments in world markets.